The Effects of Six Weeks of Patella Taping on Function, Proprioception, and Balance in Women with Knee Osteoarthritis - Maryam Alikhani; Hamid Tabatabai (Biyumikānīk-i varzishī, 2024)
Objective This study aimed to examine the effect of six weeks of patella taping on function, proprioception, and balance in women with knee osteoarthritis. Methods This applied, semi-experimental study involved middle-aged women aged 30 to 50 years. Using convenience sampling, 30 women with knee osteoarthritis from an orthopedic clinic in Tehran were selected. Participants were randomly assigned to either an experimental group (n=15) or a control group (n=15). The experimental group underwent patella taping for six weeks, while the control group continued their normal routines. Function was assessed using the WOMAC questionnaire, static balance with the single-leg stance test, dynamic balance with the Timed Up & Go test, and proprioception with the joint position sense error test. Data were analyzed using paired-sample t-tests for within-group comparisons and analysis of covariance (ANCOVA) for between-group comparisons. Results Paired-sample t-tests indicated that patella taping significantly improved pain intensity, joint stiffness, and function in the experimental group. Additionally, static and dynamic balance, as well as knee joint proprioception, showed significant improvement. ANCOVA results revealed significant post-test differences between the two groups in terms of pain intensity, joint stiffness, function, static and dynamic balance, and proprioception (p < 0.05). Conclusion The findings suggest that patella taping reduces pain and joint stiffness while improving function, balance, and proprioception in women with knee osteoarthritis. Patella taping may be an effective non-pharmacological tool for enhancing these outcomes and is recommended for use by sports trainers and physiotherapists.